Childhood adversity moderates the effect of ADH1B on risk for alcohol‐related phenotypes in Jewish Israeli drinkers. (24th October 2013) - Meyers, Jacquelyn L.; Shmulewitz, Dvora; Wall, Melanie M.; Keyes, Katherine M.; Aharonovich, Efrat; Spivak, Baruch; Weizman, Abraham; Frisch, Amos; Edenberg, Howard J.; Gelernter, Joel; Grant, Bridget F.; Hasin, Deborah
Abstract Childhood adversity and genetic variant ADH1B‐rs1229984 have each been shown to influence heavy alcohol consumption and disorders. However, little is known about how these factors jointly influence these outcomes. We assessed the main and additive interactive effects of childhood adversity (abuse, neglect and parental divorce) and the ADH1B‐rs1229984 on the quantitative phenotypes 'maximum drinks in a day' (Maxdrinks) and DSM‐Alcohol Use Disorder (AUD) severity, adjusting for demographic variables, in an Israeli sample of adult household residents (n = 1143) evaluated between 2007 and 2009. Childhood adversity and absence of the protective ADH1B‐rs1229984 A allele were associated with greater mean Maxdrinks (mean differences: 1.50; 1.13, respectively) and AUD severity (mean ratios: 0.71; 0.27, respectively). In addition, childhood adversity moderated the ADH1B‐rs1229984 effect on Maxdrinks (P < 0.01) and AUD severity (P < 0.05), in that there was a stronger effect of ADH1B‐rs1229984 genotype on Maxdrinks and AUD severity among those who had experienced childhood adversity compared with those who had not. ADH1B‐rs1229984 impacts alcohol metabolism. Therefore, among those at risk for greater consumption, e.g. those who experienced childhood adversity, ADH1B‐rs1229984 appears to have a stronger effect on alcohol consumption and consequently on risk for AUD symptom severity. Evidence for the interaction of genetic vulnerability and early life adversity on alcohol‐related phenotypes provides further insight into the complex relationships between genetic and environmental risk factors.